Theoretical investigation of optical and transport properties of organic semiconductors - Ye, Jun (2012)
Application of organic semiconductors in electronic devices has inspired and revived many academic and technological research fields. Academically, there are many unanswered questions. For example, understanding of two fundamental physical processes in organic semiconductors, i.e., the optical and charge carrier transport processes is crucial to improve the performance of materials and devices. These two processes depend on the behavior of a quasi-particle named polaron. Polaron formation occurs in organic semiconductors in which various physical processes are determined by electrons, holes or excitons coupled diagonally or off-diagonally to phonon coordinates. In this thesis, a theoretical framework which combines molecular and crystal/aggregate structures, optical spectroscopy, and charge carrier transport has been established. By applying this theoretical framework to organic semiconductors such as rubrene, optical spectra (photoluminescence and absorption) obtained from quantum-chemical calculations and corresponding measurements can be utilized to extract important material parameters. These parameters can be subsequently fed to a microscopic polaron transport model to find intrinsic transport properties. The material parameters obtained in this work are in good agreement with many well established references. More importantly, the calculated optical and transport properties, i.e., absorption spectra, photoluminescence spectra, and mobility versus temperature for molecular and single crystal rubrene agree well with the experimental results. These results reflect the success of the proposed theoretical scheme in obtaining material parameters and related properties for rubrene. Finally, future research works on improving current framework have been proposed.